Comparative effectiveness of sacubitril/valsartan versus angiotensin converting enzyme inhibitors/angiotensin receptor blockers in de novo heart failure patients. (3rd October 2022) - Taha, I; Gomme, J; Suminska, S; Schwende, H; Butylin, D; Doherty, J; Beckmeyer-Borowko, A; Farries, G
Abstract: Introduction: Effective use of pharmacological therapy in de novo heart failure (HF) patients is key for slowing down the progression of HF. Randomised clinical trials have shown sacubitril/valsartan (sac/val), providing superior benefit over renin angiotensin system (RAS) blockade with angiotensin converting enzyme inhibitors (ACEi) in patients with HF with reduced ejection fraction (HFrEF) including de novo HF patients. However, real world evidence is scarce. Purpose: To compare the rate of all-cause hospitalisations in a real world de novo HFrEF US patient population after initiating sac/val or initiating or continuing RAS blockade with ACEi or angiotensin receptor blockers (ARB) within one year of index date. Methods: This retrospective, non-interventional cohort study included adult de novo HFrEF patients (left ventricular ejection fraction ≤40%), from the Optum Electronic Health Records, from Jan 2016 to Mar 2020 (study period: Dec 2013–Mar 2021) who were prescribed sac/val or ACEi/ARB within 30 days of a new HF diagnosis. Patients either with any history of HF in the prior two years or with prior sac/val treatment were excluded. Index date was defined as the first prescription of sac/val or ACEi/ARB after a new HF diagnosis (≤30 days prior to index). One-to-two greedy propensity score matching was used to balance the study arms on demographics and clinical covariates (medications, LVEF, selected comorbidities). Negative binomial models were used to compare the primary endpoint between treatment groups and across subgroups of interest. The primary endpoint was the rate of all-cause hospitalisations within one year from index. Treatment groups were stratified by age, sex, race, ethnicity, history of myocardial infarction, comorbidities and prior ACEi/ARB treatment. Statistical analyses were conducted using R and SAS software. Results: Prior to matching, 3, 290 patients were initiated on sac/val, 47, 678 on ACEi/ARB and post-matching there were 3, 290 patients on sac/val and 6, 580 patients on ACEi/ARB. Patients with prior ACEi/ARB treatment in both the groups were 1, 597 and 2, 806, respectively. Mean age was 63.5 in sac/val and 63.7 years in ACEi/ARB groups. After propensity-score matching, the annual rate (per person-year) of all-cause hospitalisation was lower in sac/val compared with ACEi/ARB group, with incidence rate ratio (IRR) of 0.81 (95% confidence interval [CI]: 0.74–0.90) ≤1 year from index. Similarly, in the ACEi/ARB treatment naïve subgroup, sac/val treatment led to 20% reduction in the primary endpoint (IRR: 0.80, 95% CI: 0.69–0.92) compared with ACEi/ARB. Amongst subgroups, results were consistent for most, with significant reduction seen in all-cause hospitalisation rates with sac/val treatment vs. ACEi/ARB. Conclusion: Treatment with sac/val vs. ACEi or ARB significantly reduced the risk of all-cause hospitalisations in this real-world study supporting the first-line use of sac/val in treating de novo HFrEF patients. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Novartis Pharma AG